CLINICAL RECONSTRUCTION ALGORITHM USING (World Bulletin of Public Health, 2026)
Congenital craniofacial bone deformities require reconstruction strategies that respect growth restore symmetry and minimize donor site morbidity
Keywords: Congenital craniofacial deformities